Breaking the Spell of Past Misdeeds: A Hauntological Reading of The House of the Seven Gables - Justyna Fruzińska (European Journal of American Studies)
Hawthorne’s The House of the Seven Gables is a text about haunting on many levels: Hawthorne himself is haunted by his family history and by the literary influence of British gothic; the house is haunted by literal ghosts, signaling the unresolved nature of past events; the novel’s characters are haunted by the family history and their own unfulfilled futures. The book is also haunted by the Pyncheon nostalgia for the old aristocratic order, as well as by capitalist exploitation of racial and class others. This paper uses Jacques Derrida’s concept of hauntology to explore those different facets of the ghostly. As a result, the reading of Gables’ ghosts reveals a tension at the heart of the novel between a pessimistic and an optimistic reading of human life and how much it is determined by the past.